2020
DOI: 10.1002/adtp.202000212
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Biomaterial Scaffolds for Integrative Tumor Therapy and Bone Regeneration

Abstract: Bone tumors bring great pain to patients, along with a high disability rate and high mortality. Several therapeutic strategies have been applied to treat bone tumors, such as chemotherapy, radiotherapy, and surgical resection. However, these strategies have intrinsic drawbacks, such as the serious side effects of chemotherapy or the necessary reconstructive surgery of surgical resection. To help develop more satisfactory bone tumor treatment strategies, biomaterial scaffolds have been proposed. Biomaterial sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 157 publications
(280 reference statements)
0
15
0
Order By: Relevance
“…5 e and f). This phenomenon may be ascribed to the fact that high temperatures could accelerate the Fenton-like reaction [ 53 , 67 70 ]. Furthermore, we conducted the NIR laser irradiation on the Gel-SA-6CuO hydrogel scaffold during the process of methylene blue degradation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 e and f). This phenomenon may be ascribed to the fact that high temperatures could accelerate the Fenton-like reaction [ 53 , 67 70 ]. Furthermore, we conducted the NIR laser irradiation on the Gel-SA-6CuO hydrogel scaffold during the process of methylene blue degradation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, scaffolds loading two or more agents with synergistic therapy have been fabricated focusing on the combination of chemotherapy [ 37 , 38 ], immunotherapy [ 39 44 ], photothermal therapy (PTT) [ 45 47 ], magnetothermal therapy [ 34 , 48 ], chemodynamic therapy (CDT) [ 49 51 ], and so on [ 52 ]. However, the composition of scaffolds with synergistic therapy is more complicated than single modality, and complex functionalization processes are required [ 53 , 54 ]. In addition, multiple synergistic systems limit the drug loading capacity of the scaffolds for every single therapeutic agent, which often devotes considerable efforts to adjust the ratios of different drugs to achieve the best therapeutic efficiency [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that heat generation can form reactive nitrogen species (RNS) or reactive oxygen species (ROS) in the patient's body and destroy cancer cells under photodynamic therapy (PDT) or gas therapy (Figure 1C). 19 Magnetic BGCs are another group used to combat cancer. The magnetic phases/crystals are formed within the glassy matrix by controlled heat treatment, resulting in the formation of glass-ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that heat generation can form reactive nitrogen species (RNS) or reactive oxygen species (ROS) in the patient's body and destroy cancer cells under photodynamic therapy (PDT) or gas therapy (Figure 1C). 19 …”
Section: Introductionmentioning
confidence: 99%
“…Huang et al. summarized bifunctional scaffolds for tumor therapy and bone regeneration in recent years [ 34 ] and Chen et al. summarized regenerative materials related to thermal stimulation [ 35 ].…”
Section: Introductionmentioning
confidence: 99%